Assessing the contrast sensitivity function in myopic parafovea: A quick contrast sensitivity functions study - Xu, Zixuan; Zhuang, Yijing; Chen, Zhipeng; Hou, Fang; Chan, Lily Y. L.; Feng, Lei; Ye, Qingqing; He, Yunsi; Zhou, Yusong; Jia, Yu; Yuan, Junpeng; Lu, Zhong-Lin; et al. (Frontiers in Neuroscience, 2022)
Purpose Compare peripheral contrast sensitivity functions (CSF) between myopes and emmetropes to reveal potential myogenic risks during emmetropization. Materials and methods This observational, cross-sectional, non-consecutive case study included data from 19 myopes (23.42 ± 4.03 years old) and 12 emmetropes (22.93 ± 2.91 years old) who underwent central and peripheral quick CSF (qCSF) measurements. Summary CSF metrics including the cut-off spatial frequency (cut-off SF), area under log CSF (AULCSF), low-, intermediate-, and high-spatial-frequency AULCSFs (l-, i-, and h-SF AULCSFs), and log CS at 19 SFs in the fovea and 15 peripheral locations (superior, inferior, temporal, and nasal quadrants at 6, 12, 18, and 24° eccentricities, excluding the physiological scotoma at 18°) were analyzed with 3-way and 4-way between-subjects analysis of variance (ANOVA) (α = 0.05). Results Three-way ANOVA showed that myopes had significantly increased AULCSF at 6° (mean difference, 0.08; 95% CI, 0.02–0.13; P = 0.007) and 12° (mean difference, 0.09; 95% CI, 0.03–0.14; P = 0.003). Log CS at all 19 SFs were higher in the myopia group compared to the normal group (mean differencesuperior, 0.02; 95% CI, 0.01–0.20; P = 0.02 and mean differenceinferior, 0.11; 95% CI, 0.02–0.21; P = 0.01) at 12°. The h-SF AULCSF at 6° (mean differenceinferior, 1.27; 95% CI, 0.32–2.22; P = 0.009) and i-SF AULCSF at 12° (mean differencesuperior, 5.31; 95% CI, 4.35–6.27; P < 0.001; mean differenceinferior, 1.14; 95% CI, 0.19–2.10; P = 0.02) were higher in myopia vs. normal group. Conclusion We found myopia increased contrast sensitivity in superior and inferior visual field locations at 6° parafoveal and 12° perifoveal regions of the retina. The observation of increased contrast sensitivities within the macula visual field in myopia might provide important insights for myopia control during emmetropization.